MITIGATION SCENARIOS FOR RESIDENTIAL FIRES IN DENSELY POPULATED URBAN SETTLEMENTS IN SUKAHAJI VILLAGE, BANDUNG CITY - Saut Aritua Hasiholan Sagala; Praditya Adhitama; Donald Ganitua Sianturi; Umar Al Faruq (Geoplanning: Journal of Geomatics and Planning, 2016)
Residential fires are a form of disaster that often occurs in urban areas especially in densely populated settlements. This study looks at possible mitigation scenarios for this kind of disaster. A case study was conducted in Babakan Ciparay Sub-District in Bandung City, among the densely populated settlements, and was focused especially on Sukahaji Village, a sub-unit of Babakan Ciparay, which is the most densely populated village in Bandung City with up to 234.14 people/ha. There have been six structural fires recorded from 2007 until 2010 occurring in Sukahaji. This study applied stratified random sampling as the preferred sampling technique and data collection method from a total population of 3,227 buildings. The data was then examined using risk analysis. The results have led to two intervention measures suggested as mitigation scenarios for residential fires that can be applied within the Sukahaji Village. The study concludes that mitigation measures through strengthening community capacity can be the principal option in reducing risk to fires in densely populated urban settlements.